Biliary peritonitis due to a ruptured amebic liver abscess mimicking a periampullary tumor and liver metastases with the elevation of CA 19-9 and CA 125: a case report - Marin-Leiva, Javiera (2018)
Introduction: An amebic liver abscess is the most common presentation of extraintestinal amebiasis. This condition is the result of a parasite infection caused by Entamoeba histolytica. Materials and Methods: We report a case of a 53-year-old male who presented with abdominal pain in the right upper quadrant, jaundice, and a 10-kg weight loss within a 1-month span. Results and Conclusion: A wide range of symptoms and findings in the imaging tests suggestive of neoplasia, elevated levels of CA 19-9 and CA 125, and the presentation of biliary peritonitis as a complication makes this case a challenge for its approach and management.